Automated Assessment of a Students Circulatory System Functional State Using Martine's Test - Bogdan Voinyk; Galina Borisova; Vitalii Umanets; Ganna Boyko; Andrii Pavlov; Ievgen Nastenko (Innovative Biosystems and Bioengineering, 2018)
Background. The systematic self-control of students' health state allows optimizing the educational process organization of physical education and contribute improving the functioning of body systems. One of the common methods of such observation is the functional Martine's test, which provides an opportunity to investigate the dynamics of changes in blood pressure and heart rate between the resting state and every minute for five minutes after the load. In most cases, this load characteristic sufficiently fully reflects the student's cardiovascular system state. The determination of the characteristic patterns of such states will allow offering a mechanism for assessing the functional state of the circulatory system. The regular Martine's testing will allow observing the dynamics and evaluating changes in the body during the observation period.